The Types and Meanings of Idiomatic in the Begin Again Movie: Semantics Study - Diah Hayuningtyas; Meita Lukitawati Sujatna (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purposes of this paper are to identify the type of idiomatic and to know the real meaning of idiomatic while in conversation or in our daily life, idiomatic is a type of expression that’s not show the actual meaning that intended to expressed for this paper the writer will identify the idiomatic in the Begin Again movie, the researcher used qualitative method for this research. The analyzed this movie based on the theory of O’Dell & McCarthy (2010) that argued if idioms are divided into 6 types of idioms, but for this analysis the author will review only two data of every idiom, the data were taken from the conversation between the character. Finally, after analysis the movie from the script data showed that this movie contains those 6 types of idioms which are: 3 simile (4.1%), 23 proverbs (31.5%), 18 binomials (24/7%), 10 euphemism (13,7), 19 cliché and fix statement (26.0%).